Effectiveness of a Robot-Mediated Strategy While Counteracting Multidirectional Slippages. Issue 12 (14th June 2019) - Aprigliano, F.; Monaco, V.; Tropea, P.; Martelli, D.; Vitiello, N.; Micera, S.
Summary: This study investigates the effectiveness of a robot-mediated strategy aimed at promoting balance recovery after multidirectional slippages. Six older adults were asked to manage anteroposterior and mediolateral slippages while donning an active pelvis orthosis (APO). The APO was set up either to assist volunteers during balance loss or to be transparent. The margin of stability, in sagittal and frontal planes, was the main metric to assess the effectiveness of balance recovery. Results showed that the assistive strategy is effective at promoting balance recovery in the sagittal plane, for both perturbing paradigms; however, it is not effective at controlling stability in the frontal plane.